Results in the Latin America and Caribbean Region 2020, Volume 14 - World Bank (World Bank, Washington, DC, 2022)
When this booklet was prepared, COVID-19 was not part of our lexicon. Our concerns were more related to the low GDP growth of the region (close to zero) and the social unrest that we had been observing in a good number of countries. Today, however, the region is fully focused on managing the health emergency created by the COVID-19 crisis and on planning a response to the economic recession that we are entering. The World Bank Group is supporting the countries in the region. We are working on 13 COVID-19 health response operations (five of which have already been approved) using the newly-created US$6bn Fast Track Facility; and we are also engaging with governments to design appropriate economic recovery programs.